A knitted wearable flexible sensor for monitoring breathing condition. (June 2020) - Wang, Jinfeng; Soltanian, Saeid; Servati, Peyman; Ko, Frank; Weng, Ming
This article presents the development of a knitted flexible sensor, which is embedded into a seamless garment, for monitoring health condition. The sensor is designed as an elastic weft-knitted plain structure, where the conductive silver-plating filament yarn is used for breathing signal collection and the spandex core-spun yarn is used to ensure good attachment of the garment to human body. The breathing amplitude and breathing frequency are obtained from the variations in sensor resistance. The sensor can measure various kinds of breathing conditions, such as normal breathing, slow breathing, fast breathing, and shallow breathing. The results are in reasonable agreement with the actual condition. Such kind of flexible sensors have the advantages of wearable and comfort.